Osteonecrosis - R Zorzi, Alessandro; Batista de Miranda, Joao (IntechOpen, 2017)
In this book there are chapters written by great specialists, both doctors and dentists, addressing a very important subject for clinical practice and research: osteonecrosis. In addition to a general review of the subject matter in the introduction, you will find in it some subjects little discussed in other textbooks, such as osteonecrosis of the mandible and osteonecrosis of the spinal vertebrae.